PENGARUH KUALITAS AUDIT, KEKUATAN PENDAPATAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Bernadeta Nadia Septerini; Hendrani, Ai (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
Increasing the welfare of capital owners or company owners is one of the company's goals, which can be done by increasing firm value. This research aims to test audit quality, earnings power and firm size on the value of companies in the health services industry listed on the Indonesia Stock Exchange between 2019 and 2022. The research model uses a causality design and uses multiple linear regression analysis with sources. secondary data. The sampling technique used was purposive sampling, which included a total of 13 companies and 52 sets of financial report data from the health industry during the period 2019 to 2022. The findings of this research show that the combination of audit quality, firm size and earnings power simultaneously influences firm value. Audit quality does not partially influence firm value, while firm size and earnings power partially influence firm value.